A Ka‐band power amplifier with filtering characteristic for satellite communication. Issue 2 (4th October 2019) - Xie, Heng; Liu, Qiushi; Song, Bai; Fan, Yong
Abstract: This letter presents a power amplifier (PA) with the bandstop function for the satellite communication by using 0.15‐μm GaAs pHEMT process. It operates at Ka‐band (uplink at 30 GHz) and realizes the ability of filtering characteristic at K‐band (downlink at 20 GHz). In order to obtain the high suppression of this K‐band undesired frequency signal, the structure‐reused technology is adopted in this design. By using the structure reuse, the by‐pass capacitance of the decoupling circuit at each brand of the power supply is used to realize decoupling function, and then achieve the filtering characteristic at K‐band. Thanks to this structure, the whole circuit structure is simple, and it can be designed without adding other extra devices and changing the original matching topology. The miniaturization can be realized. Also, the proposed PA can operate over a wide bandwidth. The ability of high frequency suppression and the good filtering performance can be achieved over the undesired frequency band. According to the measured results, the proposed PA can operate from 28 to 35.5 GHz (23.6% relative bandwidth) and realize more than 40 dBc suppression from 18 to 22.6 GHz (22.7% relative bandwidth). In addition, the measured power‐added efficiency vs frequency is 21% to 30.8%. When the V GS is −0.45 V and the V D is 5 V, the quiescent current and the 1 dB compression point ( P −1 dB) of output are 51 mA and 18 dBm, respectively. The total area of the proposed PA with band‐stop function is 1250 μm × 850 μm.